2013
DOI: 10.1159/000356461
|View full text |Cite
|
Sign up to set email alerts
|

Adjusted Anion Gap Is Associated with Glomerular Filtration Rate Decline in Chronic Kidney Disease

Abstract: Background: Metabolic acidosis is known to accelerate the progression of chronic kidney disease (CKD). However, whether undetermined anions as indicated by the adjusted anion gap (aAG) are associated with estimated glomerular filtration rate (eGFR) decline in patients with CKD is unclear. Methods: Data from 42 patients with CKD (baseline eGFR, 7.1-52.0 ml/min/ 1.73 m2) without massive proteinuria (urinary protein-creatinine ratio, UPCR <3.5) were retrospectively analyzed. aAG was calculated from ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…In contrast, we adopted an equation for albumin-adjustment with a range similar to the usual reference [ 16 ], and hence more easily applicable. Togawa et al also analyzed 42 patients with advance CKD (eGFR 7.1–52.0 mL/min/1.73vm 2 ) for the association between A-SAG and CKD progression [ 13 ]. Although they suggested that A-SAG was significantly associated with delta eGFR/6 months in multiple linear regression (beta 0.45, P < 0.01), they did not evaluate the association with mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, we adopted an equation for albumin-adjustment with a range similar to the usual reference [ 16 ], and hence more easily applicable. Togawa et al also analyzed 42 patients with advance CKD (eGFR 7.1–52.0 mL/min/1.73vm 2 ) for the association between A-SAG and CKD progression [ 13 ]. Although they suggested that A-SAG was significantly associated with delta eGFR/6 months in multiple linear regression (beta 0.45, P < 0.01), they did not evaluate the association with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…SAG is elevated and related to mortality even in early kidney disease [ 12 ], and high SAG is associated with CKD progression [ 13 ]. Therefore, we hypothesized that SAG might predict mortality in advanced CKD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Deteriorated kidney functions, decreased GFR, and increased SAG levels were observed, and it has been suggested that increased ACAG may be an independent predictor of CKD [ 24 ]. Patients with CKD and high SAG have worse cardiovascular outcomes, which may result from cardiovascular damage caused by accumulated uremic anions.…”
Section: Discussionmentioning
confidence: 99%
“…Une étude japonaise a montré l'intérêt du TAPc pour prédire un retour à une activité cardiaque spontanée dans la réanimation de l'arrêt cardiocirculatoire, avec une meilleure valeur prédictive pour le TAPc (AUC à 0,871 ; Se = 86 % ; Spé = 75 %) que pour le TAP (AUC à 0,850 ; Se = 82 % ; Spé = 69 %), et une valeur de TAPc élevée (> 30 mEq/l) était en défaveur d'une récupération de l'arrêt cardiaque [34]. Enfin, dans la population des patients insuffisants rénaux chroniques, il existerait un intérêt pronostique du TAPc [35], pouvant être considéré comme un marqueur du déclin du débit de filtration glomérulaire et de la progression de la maladie rénale chronique [36], avec une bonne corréla-tion à l'accumulation de toxines urémiques.…”
Section: Tap Corrigé à L'albumineunclassified